Penerapan Pencatatan Keuangan Digital Dalam Kinerja UMKM Di Pasar Gedangan - Sherly Aulia Yunianti; Mochammad Ilyas Junjunan; Rianto Anugerah Wicaksono (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2026)
Digital transformation in financial management has become an essential factor in improving the competitiveness of Micro, Small, and Medium Enterprises (MSMEs), particularly within traditional market sectors. This study aims to analyze the effect of implementing digital financial record-keeping on the performance of MSMEs in Gedangan Market, Sidoarjo. The research employed a qualitative approach using a descriptive case study design. Data were collected through in-depth interviews, observations, and documentation involving ten MSME owners who had utilized digital financial recording applications for at least six months. Data analysis was conducted using thematic analysis to identify major patterns and themes related to changes in business financial management. The findings indicate that the implementation of digital financial record-keeping improves transaction management efficiency, financial information accuracy, cash flow control, and supports faster and more accurate business decision-making. In addition, digital systems enhance business transparency and accountability, which contribute to improved MSME performance. However, technology implementation still faces several challenges, including limited digital literacy, inadequate access to devices, and resistance to change. This study contributes to the growing literature on MSME digital transformation in traditional market contexts and highlights the importance of continuous training and assistance programs to support the adoption of digital financial technology.